Veritas - Seminari Alkitab Asia Tenggara (Seminari Alkitab Asia Tenggara, 2000)
Evangelical theology that focuses on the novelty in the field of biblical studies, systematic theology, and practical theology which aims to contribute to theological studies and ecclesial ministry.
Keywords: Theology : Periodicals; Theology : Indonesia : Periodicals; Christianity : Indonesia : Periodicals; Evangelicalism : Periodicals; Théologie : Périodiques; Théologie : Indonésie : Périodiques; Christianisme : Indonésie : Périodiques; Évangélisme : Périodiques; Theology; Evangelicalism; Christianity; Indonesia